Truth and metaphor and their implications - Marzuki, Muhammad Nabil; Zaharan, Mohammad Fawwaz; Zaki, Muhammad Shahrulnaim; Mohd Sufian, Muhammad Sufi Soulhi (2025)
Slide presentation for "Truth and metaphor and their implications"